Utilization of audiovisual media for training by La Crosse, Wisconsin employers - Peters, James (My University, 1973)
The study involved contacting La Crosse, Wisconsin employers to determine their use of audiovisual media in the training of employees. A questionnaire was provided asking information related to the training programs of the Individual employers. The questions were designed to provide an insight into the general attitudes of the employers toward education, and more specifically, to observe the employers use of audiovisual media in the training programs. The information needed was collected through personal interviews, or in some special situations by telephone conversations. The sample consisted of eighty-nine employers from the La Crosse area. Each of these were contacted and it was ascertained that seventeen employers, 19.12 percent of the sample, used some form of audiovisual media for employee education. During February and March of 1973, these seventeen employers were interviewed and the resulting information was compiled. From the data collected, appropriate tables were constructed and various aspects of using audiovisual media for training were discussed. Analysis of the data received indicated that the most popular forms of audiovisual media used by the seventeen employers interviewed were 16mm film projectors and videotape systems. The reasons given for this preference were availability, adaptability, flexibility, and versatility of the mediums. The employers revealed that there was an increased need for software in most of their specialized areas. They also made reference to the cost factor of using audiovisual material; they said it was expensive and did not reduce the cost of training. They agreed that using media did make the training of personnel more effective. The use of media was considered beneficial by all of the employers interviewed. Future use of media will depend on cost and availability of material. There was a great deal of enthusiasm concerning the use of media, especially the more recent development of video equipment. A number of employers mentioned this as a form of media they were Interested in acquiring for training purposes. In general, the study provided information used to conclude that the use of audiovisual media in industrial education for the La Crosse area is similar In nature to the use of media in the schools. There were several cases where employers had adapted audiovisual media for specific individualized needs.
Keywords: Employees -- Training of -- Wisconsin -- La Crosse; Occupational training -- Wisconsin -- La Crosse -- Audio-visual aids